Food culture ('uruf) among Muslim community in Borneo: an exploratory research - Abdul Rahman, Russly; Ab Rahman, Suhaimi; Ramli, Mohd Anuar; Jamaludin, Mohammad Aizat; Yaacob, Halimatus Saadiah (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Every society is reflected by the culture that they had practiced one of it, is in halal food culture (‘uruf). This study explores the Muslim community in Sabah for the practiced of halal food culture. To obtain data on the research, researchers have applied the method of literature and field. This study found that Muslim communities in Sabah do have awareness about halal but still in a low level of understanding the concepts include, dietary food sources and its guiding principles. Most Sabahan people prefer to have fresh seafood such as fish, shrimp and seaweed in their regular diet. This even coincide with the local geography, which mostly they inhabit the coastal area and in island. Hence this exploratory study was to describe more clearly about the dietary food in halal food culture that is applied by the Muslim community.